Integrated assessment of water quality and trophic status in High Altitude Andean lagoons: a multi-index and multivariate approach for sustainable fish farming management - Custodio, María (2026)
High-altitude Andean lagoons are ecologically sensitive systems whose water quality is under increasing pressure from the expansion of aquaculture and other human activities. An integrated assessment of water quality and trophic status was carried out in three lagoons located in the highlands of central Peru, using a multi-index and multivariate approach that combined physicochemical parameters, trophic indices (TRIX, TSI, molar N:P ratio), and heavy-metal indices, evaluated against Peruvian EQS, USEPA, and CCME water-quality standards. Principal component analysis explained 60.1% of the total variability, with the first axis (40.4%) structured by an organic loading and nutrient gradient that consistently separated Tipicocha from the other lagoons. Total phosphorus in Tipicocha reached concentrations well above the Peruvian EQS threshold, and TRIX values classified all lagoons as eutrophic to hypertrophic (5.46–6.21). TSI (TP) classified Tipicocha and Tranca Grande as hypereutrophic, whereas TSI (Chl-a) remained within the eutrophic range (53–60), a pattern consistent with additional environmental constraints on phytoplankton biomass. Molar N:P ratios indicated strong nitrogen limitation in Tipicocha and Tranca Grande, whereas Pomacocha showed a seasonal shift from co-limitation during the dry season to potential nitrogen limitation during the rainy season. Metal contamination was low according to EQS and USEPA criteria, whereas CCME thresholds suggested moderate to high contamination (HPI up to 105.1), with systematic exceedances of Cd, Cu, and Zn at all sites. Taken together, the results point to strong trophic enrichment associated with fish-farming activity as the main pressure on water quality in these ecosystems and show that the choice of regulatory framework has a decisive influence on metal-risk classification.